2010
DOI: 10.1007/s10658-010-9657-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microorganisms associated with atypical superficial blemishes of potato tubers and pathogenicity assessment

Abstract: Skin blemishes of potato (Solanum tuberosum L.) tubers can cause severe economical losses to production. Some blemishes are due to known pathogens and others whose causes are unknown are called atypical blemishes. The present work aims at determining the origin of superficial atypical blemishes on a set of 204 tubers coming from 12 different French regions producing potato. The diversity of fungi and Streptomyces bacteria associated with blemishes was investigated by systematic isolation followed by identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
(25 reference statements)
1
34
0
2
Order By: Relevance
“…The fungal genera Alternaria, Clonostachys, Fusarium, Penicillium and Rhizoctonia are cited to be commonly encountered in both the rhizosphere and the geocaulosphere of potato (Pieta & Patkowska, 2003; Fiers et al , 2010), and >60 bacterial genera have been identified by culture‐dependant methods in different potato cultivars (Table 1). Three genera, known to mainly contain rhizobacteria species, were consistently identified in each microenvironment: Agrobacterium, Bacillus and Pseudomonas .…”
Section: Potato Rhizosphere Endorhiza and Microbial Communitymentioning
confidence: 99%
“…The fungal genera Alternaria, Clonostachys, Fusarium, Penicillium and Rhizoctonia are cited to be commonly encountered in both the rhizosphere and the geocaulosphere of potato (Pieta & Patkowska, 2003; Fiers et al , 2010), and >60 bacterial genera have been identified by culture‐dependant methods in different potato cultivars (Table 1). Three genera, known to mainly contain rhizobacteria species, were consistently identified in each microenvironment: Agrobacterium, Bacillus and Pseudomonas .…”
Section: Potato Rhizosphere Endorhiza and Microbial Communitymentioning
confidence: 99%
“…Detection of dry rot (Fusarium spp.) and black scurf (Rhizoctonia solani) was done using methods described by [26] and [27] respectively. Three seed tubers per sample were randomly drawn and washed under running tap water.…”
Section: Determination Of Tuber-borne Infectionmentioning
confidence: 99%
“…Highly viable seed and soil borne inocula of Rhizoctonia solani are carried in the soil or in infected tubers leading to spread of the disease [17,60,61]. Seed tubers infected with dry rot, black scurf and other fungal pathogens causes high storage losses through rotting and reduction in marketability of the ware potato due to formation of blemishes on skin of tubers [26,59,62].…”
Section: Physical Quality and Infection With Tuber-borne Disease Pathmentioning
confidence: 99%
“…Originária dos Andes e considerada uma das quatro principais espécies cultivadas, a batata (Solanum tuberosum L.) é a base da alimentação da população de diversos países e culturas (Fiers et al 2010).…”
unclassified
“…Apesar de o fungo A. solani, geralmente, ser retratado como o agente causal da pinta preta (Yanar et al 2011, Leiminger & Hausladen 2012, Weber & Halterman 2012, outras espécies do gênero também podem estar associadas à doença, como A. alternata (Cwalina-Ambroziak & Bogucka 2012) e A. grandis (Rodrigues et al 2010).…”
unclassified